Determinant Factors of Turnover Intention with Organizational Commitment as a Mediating Variable - Fida Yuyun Nur Safaah; Mila Fursiana Salma Musfiroh; Titik Hinawati (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Objective - This study aims to determine the effect of work stress and job satisfaction variables on turnover intention through organizational commitment as a mediator. Method - This study uses a quantitative research method. The population in this study were 30 employees of LKMS BTM Surya Amanah Temanggung. The sampling technique used was total sampling, namely a sampling technique with the entire population, namely 30 employees of LKMS BTM Surya Amanah Temanggung as respondents. Data collection used observation and questionnaires. The data obtained were then analyzed using the Structure Equation Modeling (SEM) analysis technique with the Partial Least Square (PLS) approach through SmartPLS 4.0 software. Results - The results of the study showed that work stress had a positive effect on turnover intention, job satisfaction did not affect turnover intention, work stress did not affect organizational commitment, job satisfaction had a positive effect on organizational commitment, organizational commitment did not affect turnover intention, and organizational commitment was unable to mediate work stress and job satisfaction on turnover intention of LKMS BTM Surya Amanah Temanggung employees. Implications - This study uses data from employees of LKMS BTM Surya Amanah Temanggung. Originality - This paper examines the relationship between several factors that influence employee turnover intention at LKMS BTM Surya Amanah Temanggung. The number of employees who do turnover retention illustrates the organizational commitment of employees of LKMS BTM Surya Amanah in Temanggung.